Implementation of Digital Transformation and Government Enterprise Architecture in Improving the Performance of Integrated Social Services - Ekarini, Mira Indriyulia; Rahayu, Agus; Disman, Disman; Wibowo, Lili Adi (Universitas Padjadjaran, 2024)
This study addresses the subject matter of declining public confidence in local governments in Indonesia, primarily due to issues in public service delivery, highlighting the urgent need for improved integrated social services. The objective is to analyze the mediating effect of enterprise architecture orientation on the influence of environmental turbulence, flexibility strategy, business model innovation, and digital transformation on social service performance in West Java. Methods involved a survey explanatory approach with all 27 social service providers in West Java Province, employing whole population sampling. Data were analyzed using descriptive statistical analysis and hypothesis testing using Partial Least Square Structural Equation Modeling (PLS-SEM). Results indicate that environmental turbulence, flexibility strategy, business model innovation, and digital transformation significantly impact social service performance when mediated by enterprise architecture orientation. The conclusions suggest that a robust model emphasizing strategic architectural orientation and effective implementation of flexibility, innovation, and digital transformation can enhance social service performance amidst environmental challenges. This study contributes to understanding the complex dynamics of social service provision in local governments, advocating for strategic investments in enterprise architecture and adaptive strategies to improve public service delivery and restore public trust.